A long walk to water - Park, Linda Sue. (Boston : Sandpiper/Houghton Mifflin Harcourt, 2011)
When the Sudanese civil war reaches his village in 1985, eleven-year-old Salva becomes separated from his family and must walk with other Dinka tribe members through southern Sudan, Ethiopia, and Kenya in search of a safe haven. Based on the life of Salva Dut, who, after emigrating to America in 1996, began a project to dig water wells in Sudan.
"Based on a true story"--T.-p.
720
Keywords: Dut, Salva, -- 1974- -- Juvenile fiction; Refugees -- Juvenile fiction; Survival -- Juvenile fiction; Water -- Juvenile fiction; Black people -- Sudan -- Juvenile fiction